2020
DOI: 10.1136/bmjopen-2020-037117
|View full text |Cite
|
Sign up to set email alerts
|

Turnover intention among primary health workers in China: a systematic review and meta-analysis

Abstract: ObjectivesTo analyse the prevalence and determinants of turnover intention (TI) among primary health workers (PHWs) in China to provide evidence for improving retention measures.DesignSystemic review and meta-analysis.Data sourcesFour English-language databases (PubMed, EMBASE, Cochrane Library, PsycINFO) and three Chinese databases (CNKI, CSPD, CBM) were searched up to October 2019.Eligibility criteriaEligible studies were observational or descriptive studies conducted in mainland China. The prevalence of TI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 55 publications
9
75
1
3
Order By: Relevance
“…Increasing turnover intention among healthcare workers in the era of the COVID-19 pandemic has been of intense concern in China and countries badly impacted by the COVID-19 pandemic [ 9 , 14 ]. In China, the healthcare system was challenged by a shortage of medical doctors even before the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing turnover intention among healthcare workers in the era of the COVID-19 pandemic has been of intense concern in China and countries badly impacted by the COVID-19 pandemic [ 9 , 14 ]. In China, the healthcare system was challenged by a shortage of medical doctors even before the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the socio-economic variables did not significantly predict turnover intention in the multivariable analysis, however, turnover intention was significantly higher among participants from rural and lower household monthly income in the univariable analysis. Remuneration is negatively associated with turnover intention in most industries, likewise in healthcare services [ 14 ]. Students from lower socio-economic backgrounds exhibited higher turnover intention perhaps due to a desire for a higher paid profession.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary health care system has been significantly improved following its reform since 2003. Nevertheless, challenges remain, including frequent staff turnover [81], and the CDC system, created in 2003 with a goal to strengthen the public health service, struggles to maintain the necessary levels of technical expertise. Between 2003 and 2018, the number of personnel and professionals reduced by 10.6 and 12.2%, respectively, for various reasons, including low salary [82].…”
Section: Challenges To Maintaining Malaria-free Statusmentioning
confidence: 99%
“…For medical personnel, the investment of time and money and the difficulty of obtaining a professional title [ 50 ] make them sensitive to remuneration and development issues. In addition, previous studies [ 26 , 54 , 55 ] have reported that remuneration and development are also important factors that affect the work satisfaction and enthusiasm of community health workers. Therefore, we recommended that the sense of gain of medical personnel seeking employment at PMHCIs can be increased through appropriate remuneration and development opportunities.…”
Section: Investigationmentioning
confidence: 99%